Dynamics of Staphylococcus aureus Cas9 in DNA target Association and Dissociation - Zhang, Siqi; Zhang, Qian; Hou, Xi‐miao; Guo, Lijuan; Wang, Fangzhu; Bi, Lulu; Zhang, Xia; Li, Hai‐hong; Wen, Fengcai; Xi, Xu‐guang; Huang, Xingxu; Shen, Bin; et al. (EMBO reports, 2020)
Staphylococcus aureus Cas9 (SaCas9) is an RNA-guided endonuclease that targets complementary DNA adjacent to a protospacer adjacent motif (PAM) for cleavage. Its small size facilitates in vivo delivery for genome editing in various organisms. Herein, using single-molecule and ensemble approaches, we systemically study the mechanism of SaCas9 underlying its interplay with DNA. We find that the DNA binding and cleavage of SaCas9 require complementarities of 6and 18-bp of PAM-proximal DNA with guide RNA, respectively. These activities are mediated by two steady interactions among the ternary complex, one of which is located approximately 6 bp from the PAM and beyond the apparent footprint of SaCas9 on DNA. Notably, the other interaction within the protospacer is significantly strong and thus poses DNA-bound SaCas9 a persistent block to DNA-tracking motors. Intriguingly, after cleavage, SaCas9 autonomously releases the PAM-distal DNA while retaining binding to the PAM. This partial DNA release immediately abolishes its strong interaction with the protospacer DNA and consequently promotes its subsequent dissociation from the PAM. Overall, these data provide a dynamic understanding of SaCas9 and instruct its effective applications.